PHRASEOLOGICAL UNITS IN MEDICINE (American Journal of Interdisciplinary Research and Development, 2024)
The article analyzes phraseological phrases used in medicine and their role in the formation of professional qualities of a future doctor. We will also look at the experiences of other doctors.